2017
DOI: 10.1039/c7ra03388e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing menaquinone-7 production in recombinant Bacillus amyloliquefaciens by metabolic pathway engineering

Abstract: Six key enzymes are vital for MK-7 production, but the same enzyme has different effect on MK-7 production in different cultivating methods. Thus, the high enzyme activity and high-traffic biosynthetic pathway are beneficial to synthesize MK-7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
4
22
0
Order By: Relevance
“…Similar results were observed from the overexpression of 1,4-dihydroxy-2-naphthoate octaprenyltransferase(MenA) in B. subtilis 168 and E. coli increased the Vitamin K2 content, in which imply that the reaction of converting 1,4-Dihydroxy-2-naphthoate to 2-Demethylmenaquinone plays the most important role in increasing Vitamin K2 production [33][34][35]. Therefore, the enzyme MenA was listed as rate-limiting enzymes of the Menaquinone pathway.…”
Section: Discussionsupporting
confidence: 70%
“…Similar results were observed from the overexpression of 1,4-dihydroxy-2-naphthoate octaprenyltransferase(MenA) in B. subtilis 168 and E. coli increased the Vitamin K2 content, in which imply that the reaction of converting 1,4-Dihydroxy-2-naphthoate to 2-Demethylmenaquinone plays the most important role in increasing Vitamin K2 production [33][34][35]. Therefore, the enzyme MenA was listed as rate-limiting enzymes of the Menaquinone pathway.…”
Section: Discussionsupporting
confidence: 70%
“…cremoris. Firstly, enhanced expression of menA result in around 2-fold higher MK production in E. coli, B. amyloliquefaciens, E. meningoseptica, and B.subtilis (Kong and Lee, 2011;Liu et al, 2017Liu et al, , 2018Xu et al, 2017;Ma et al, 2019;Yang et al, 2019) and we found that this also applies for L. lactis. More MenA activity will pull out products of both the menaquinone and MEV+PP pathways possibly leading to an increased flux through both pathways.…”
Section: Discussionmentioning
confidence: 62%
“…They include optimization of the fermentation process, increasing menaquinone secretion, improving bioreactor design, directed mutagenesis of strains or genetic engineering of strains (Ren et al, 2019). To enhance strain performance genomic changes has been made in order to maximize substrate pools, limit the production of by-products, overexpress key genes, express novel pathways, or combinations of the aforementioned strategies (Kong and Lee, 2011;Liu et al, 2017Liu et al, , 2018Xu et al, 2017;Ma et al, 2019;Yang et al, 2019). Most of these studies have been performed using B. subtilis, B. amyloliquefaciens, E. meningoseptica, or E. coli and seek to produce menaquinone on an industrial scale for use as a nutritional supplement or food additive.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of them has any catalytic activity unless they are combined . Overexpression of HepS in B. subtilis 168 could increase the MK‐7 production, while overexpression of HepS in B. amyloliquefaciens Y‐2 led to a greater increase in the MK‐7 production than that of other enzymes …”
Section: Resultsmentioning
confidence: 99%